2017
DOI: 10.1038/s41467-017-01584-3
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule multiplexed nanopore protein screening in human serum using aptamer modified DNA carriers

Abstract: The capability to screen a range of proteins at the single-molecule level with enhanced selectivity in biological fluids has been in part a driving force in developing future diagnostic and therapeutic strategies. The combination of nanopore sensing and nucleic acid aptamer recognition comes close to this ideal due to the ease of multiplexing, without the need for expensive labelling methods or extensive sample pre-treatment. Here, we demonstrate a fully flexible, scalable and low-cost detection platform to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
208
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(211 citation statements)
references
References 53 publications
2
208
0
1
Order By: Relevance
“…The successful assembly of DNA origami folding from an M13mp18 ssDNA scaffold following previous reports [16,18] was confirmed by atomic force microscopy (AFM). Figure 2 shows representative examples of all four assembled DNA origami structures.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The successful assembly of DNA origami folding from an M13mp18 ssDNA scaffold following previous reports [16,18] was confirmed by atomic force microscopy (AFM). Figure 2 shows representative examples of all four assembled DNA origami structures.…”
Section: Resultssupporting
confidence: 68%
“…Moreover, the adaptation of the nanopipette with a DNA origami "gate" structure has been shown to enable the orchestration of controlled DNA translocation. [15] An alternative strategy for single-molecule sensing employed by Edel et al involved protein detection using nucleic aptamer-modified DNA carriers [16] and DNA aptamer-functionalized gold nanoparticles. [15] An alternative strategy for single-molecule sensing employed by Edel et al involved protein detection using nucleic aptamer-modified DNA carriers [16] and DNA aptamer-functionalized gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Meervelt et al [117] carried out a similar experimental study by using ClyA nanopores to study the interaction between the G-quadruplex fold of the thrombin binding aptamer (TBA) and human thrombin (HT). In 2017, Sze et al [118] demonstrated simultaneous nanopore-based detection of multiple protein targets each bound to a specific aptamer hybridizing to a specific segment of a dsDNA (Fig. 8).…”
Section: Specific Interactions Between Proteins and Ssdna/dsdnamentioning
confidence: 99%
“…Sze et al. developed a rapid and simple aptamer assay that grafts a selective binding region to a long λ‐DNA carrier . This work is also noteworthy because it demonstrates the possibility of nanopore sensing in complex physiological fluids.…”
Section: Protein Sensingmentioning
confidence: 99%